Pengaruh Model Pembelajaran Project Based Learning (PjBL) Terhadap Motivasi Belajar IPA Kelas V SD Negeri Ciruyung 01 - Ningsih, Sulistiya; Febriyani, Shoimatun; Azizah, Amalia Nurul (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of Project Based Learning (PjBL) on science’s learning motivation of class V SD Negeri Ciruyung 01. The method of the research is quantitative pre-experimental design with one-group pretest-posttest design. The research subjects were 26 students. The data collection was taken by pretest and posttest questionnaires, and observation sheets for the implementation of learning. The analysis of the questionnaire data in this study used a paired samples t-test hypothesis test. From the results of the data analysis, a significance level of 0.000 was obtained. These results indicate that 0.000 < 0.05 at a 95% confidence level, so that Ha can be accepted and H0 is rejected. This result is also reinforced by the statement in point 2 about the feeling of pleasure in being given project assignments, which received the highest percentage of 98%. Therefore, it can be concluded that the Project Based Learning (PjBL) learning model has an effect on student learning motivation.